Aesthetics and Politics in the films of Kongdej Jaturanrasmee - Boon-arch, Surasak (Asian Creative Architecture, Art and Design, 2021)
The objectives of this qualitative research aims are to study aesthetics and politics in the films of Kongdej Jaturanrasmee. A film director who conveys the story of Thai society with tact and depth through multi-dimensional of films. This is a study of the textual analysis of 7 selected films including Sayew (2003),Midnight My Love (2005), Handle Me with Care (2008), P047 (2011), Tang Wong (2013), Snap (2015) and Where We Belong (2019). The film selection criteria were based on feature films, the event related to the political period in Thailand between 1992-2019, and awards won or widespread recognition. The research results found that all 7 selected films shared the following common traits: 1) aesthetics or beauty in films, it’s classified as a neorealism, it's an art that conveys meaning to allow the audience to interpret the film within the framework of their own experience. Under the aesthetic aspect, visual and sound symbols is often used through the characters that are diverse in gender, class, occupation and generations. 1.1) The beauty of visual elements conveys the feelings of a nostalgic character who wants to escape the truth in search of love and happiness. This element is presented through simple editing methods in storytelling, emphasize the emotions and using pictures alternating with letters. 1.2) Meanwhile, the beauty of sound elements uses the power of silence instead of speaking through conversations and movie soundtracks to convey more meaning. 2) Politics in films: The analyzed films presented significant political implications in each time and place in Thailand. That’s conveys denotation and connotation. Thus, Jaturanrasmee’s films went beyond entertainment purposes but also for understanding human diversity and being archival, reflecting the diversity of people in Thai society. 2.1) Jaturanrasmee’s earlier film production between 2003-2008 used only political events as a background. During this era, different symbols had been used, such as the Thai national flag and the Thai national anthem, which are not directly related to political content. 2.2) In his later film production between 2011-2019, the nature of asking questions about the events that have occurred in Thai society emerged, mainly presenting the development of communication technology that characters are used in each story to reduce the stress of politics and thus recording Thailand's extraordinary political history through films.